The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/21691401.2021.1902337
|View full text |Cite
|
Sign up to set email alerts
|

Targeting regulation of the tumour microenvironment induces apoptosis of breast cancer cells by an affinity hemoperfusion adsorbent

Abstract: The cytokine network of tumour microenvironment (TME) plays an important role in cancer growth and progression. The current work aims to provide a new strategy for cancer therapy based on the targeted regulation of cytokines in the TME. Here, heparin-coupled polyvinyl alcohol (PVA-H) microspheres have been developed as an adsorbent for selectively remove tumour-induced immunosuppressive cytokines, such as vascular endothelial growth factor (VEGF) and transforming growth factor-beta (TGF-b), but not tumour necr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Although not yet applied in the clinic, affinity adsorbents have been adopted to selectively remove immunosuppressive cytokines, which may be a promising strategy for cancer treatment. It has been revealed that the cytokine network of the TME is involved in tumor progression and metastasis, leading Wang et al further to utilize polyvinyl alcohol (PVA) microspheres coupled with heparin to remove tumor-induced cytokines 113 . The developed approach efficiently adsorbed immunosuppressive cytokines, such as VEGF and TGF-β, in the blood of tumor patients, facilitating cancer therapy.…”
Section: Clearance Strategies For Tdesmentioning
confidence: 99%
“…Although not yet applied in the clinic, affinity adsorbents have been adopted to selectively remove immunosuppressive cytokines, which may be a promising strategy for cancer treatment. It has been revealed that the cytokine network of the TME is involved in tumor progression and metastasis, leading Wang et al further to utilize polyvinyl alcohol (PVA) microspheres coupled with heparin to remove tumor-induced cytokines 113 . The developed approach efficiently adsorbed immunosuppressive cytokines, such as VEGF and TGF-β, in the blood of tumor patients, facilitating cancer therapy.…”
Section: Clearance Strategies For Tdesmentioning
confidence: 99%
“…Xiong et al developed porous PLGA microspheres loaded with natural drugs using the solvent evaporation method from an emulsion, introducing an innovative approach for lung cancer treatment through drug delivery [ 28 ]. Wang et al utilized heparin-coupled PVA microspheres as adsorbents to selectively eliminate tumor-induced immunosuppressive cytokines [ 29 ]. These studies not only showcase the diverse applications of synthetic polymers in medicine but also introduce innovative ideas and techniques for future cancer therapy.…”
Section: Polymer Microspheres Overviewmentioning
confidence: 99%
“…For example, a polymeric carrier made of sodium alginate combined with chitosan encapsulating a transforming growth factor-β (TGF-β) receptor inhibitor and E. coli induced apoptosis of tumor cells and differentiation of immune cells in the intestine, thereby enhancing the immunotherapeutic effect [ 77 ]. Selective depletion of immunosuppressive cytokines, such as using heparin-coupled PVA microspheres to remove vascular endothelial growth factor (VEGF) and TGF-β, has shown significant antiproliferative and pro-apoptotic effects on breast cancer cells [ 29 ]. Hence, selective depletion of immunosuppressive cytokines holds promise as a strategy for cancer treatment.…”
Section: Polymer Microspheres In Cancer Applicationsmentioning
confidence: 99%